Penerapan Metode Weighted Aggregated Sum Product Assessment Dalam Menentukan Tepung Terbaik Untuk Memproduksi Bihun - Elvina D Marbun; Lilis A Sinaga; Endang Ria Simanjuntak; Dodi Siregar; Joli Afriany (STMIK Budi Darma, 2018)
Flour is one of the basic ingredients of composite flour and consists of carbohydrates, fats, proteins, minerals and vitamins. Flour is semi-finished products for further industrial raw materials. Flour is a solid particle in the form of fine grains and even very fine depending on its use. Flour is usually used for industrial raw materials, research purposes, or used in household needs, such as making cakes and bread. To make flour takes 12 hours by way of rice soaked in clean water, drained, dried, mashed and sieved using a sieve 80 mesh. Decision support systems are built to support a solution or a problem for an opportunity. In determining the best flour used decision support system. In addition, the advantages in determining the flour, in order to assist the company in choosing the best flour for vermicelli production in order to create the best quality. Application in the Weighted Aggregated Sum Product Assessment method will assist in determining the best flour for Vermicelli production.